3C-SiC microdisk mechanical resonators with multimode resonances at radio frequencies. (6th June 2017) - Lee, Jaesung; Zamani, Hamidrera; Rajgopal, Srihari; Zorman, Christian A; Feng, Philip X-L
Abstract: We report on the design, modeling, fabrication and measurement of single-crystal 3C-silicon carbide (SiC) microdisk mechanical resonators with multimode resonances operating at radio frequencies (RF). These microdisk resonators (center-clamped on a vertical stem pedestal) offer multiple flexural-mode resonances with frequencies dependent on both disk and anchor dimensions. The resonators are made using a novel fabrication method comprised of focused ion beam nanomachining and hydroflouic : nitric : acetic (HNA) acid etching. Resonance peaks (in the frequency spectrum) are detected through laser-interferometry measurements. Resonators with different dimensions are tested, and multimode resonances, mode splitting, energy dissipation (in the form of quality factor measurement) are investigated. Further, we demonstrate a feedback oscillator based on a passive 3C-SiC resonator. This investigation provides important guidelines for microdisk resonator development, ranging from an analytical prediction of frequency scaling law to fabrication, suggesting RF microdisk resonators can be good candidates for future sensing applications in harsh environments.